2023
DOI: 10.3390/atmos14091398
|View full text |Cite
|
Sign up to set email alerts
|

Variability of Air Pollutant Concentrations and Their Relationships with Meteorological Parameters during COVID-19 Lockdown in Western Macedonia

Paraskevi Begou,
Vasilios Evagelopoulos,
Nikolaos D. Charisiou

Abstract: The lockdown implemented to tackle the spread of the COVID-19 pandemic had a positive impact on air quality. Globally, studies have shown that air pollutant levels decreased temporally during the restriction measures. In this study, we evaluated the impact of COVID-19 restrictions on the air quality of Western Macedonia, Greece, using the concentrations of PM2.5 and PM10 along with meteorological data from the Air Quality Monitoring Stations (AQMS) operated by the Lignite Center of Western Macedonia. In Wester… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 46 publications
1
2
0
Order By: Relevance
“…Moreover, the PM10 and PM2.5 percentage reductions, almost in all cases examined, were higher in the period 2001-2009, compared to the period 2010-2019 and the entire period 2001-2019. Finally, these decreases in the concentrations of both PM10 and PM2.5 levels, during the months of the restrictive measures due to the COVID-19 pandemic, in all major Greek cities were similar to the results of other researchers in Greek urban areas [19][20][27][28][29][30].…”
Section: Pm10 Industrial Stationssupporting
confidence: 88%
See 1 more Smart Citation
“…Moreover, the PM10 and PM2.5 percentage reductions, almost in all cases examined, were higher in the period 2001-2009, compared to the period 2010-2019 and the entire period 2001-2019. Finally, these decreases in the concentrations of both PM10 and PM2.5 levels, during the months of the restrictive measures due to the COVID-19 pandemic, in all major Greek cities were similar to the results of other researchers in Greek urban areas [19][20][27][28][29][30].…”
Section: Pm10 Industrial Stationssupporting
confidence: 88%
“…As far as the Greek region, the studies for the ΡΜ10 and ΡΜ2.5 levels showed a decrease of PM2.5 concentrations, up to 18%, in the Greater Area of Athens [27], while in the city of Volos, a reduction of 37.4% in mean daily PM2.5 concentration was found, according to Kotsiou et al [28] and also, a decrease, up to 24%, for the ΡΜ10 concentrations in the city center of Athens [29]. Furthermore, on the air of Western Macedonia, according to Begou et al [30], a decrease in average PM2.5 concentrations was found, ranging from −1% to −36% and a higher decrease in average PM10 concentrations ranging from −13% to −40% was found.…”
Section: Introductionmentioning
confidence: 92%
“…A survey carried out in Volos, Greece, has shown a substantial reduction of 37.4% in the pollution load throughout the three phases of the COVID-19 pandemic in 2020, compared to 2019 23 . Another study carried out in Western Macedonia, Greece, noted that the concentrations of and experienced a predominant decrease in the years 2020 and 2021 during the lockdown periods, a decrease was found in the average concentrations of that varied between − 1 and − 36%, while the average concentrations of showed an even more pronounced reduction, fluctuating between − 13 and − 40% 24 . A study carried out in Bhubaneswar, India, throughout the entire lockdown phase, revealed a 42.35% reduction in and 45% in 25 .…”
Section: Introductionmentioning
confidence: 96%